After the fact : two countries, four decades, one anthropologist - Geertz, Clifford (Cambridge, Mass. : Harvard University Press, 1995)
"Suppose," Clifford Geertz suggests, "having entangled yourself every now and again over four decades or so in the goings-on in two provincial towns, one a Southeast Asian bend in the road, one a North African outpost and passage point, you wished to say something about how those goings-on had changed." A narrative presents itself, a tour of indices and trends, perhaps a memoir?
None, however, will suffice, because in forty years more has changed than those two towns - the anthropologist, for instance, anthropology itself, even the intellectual and moral world in which the discipline exists.
To view his two towns in time, Pare in Indonesia and Sefrou in Morocco, Geertz adopts various perspectives on anthropological research and analysis during the post-colonial period, the Cold War, and the emergence of the new states of Asia and Africa. Throughout, he clarifies his own position on a broad series of issues at once empirical, methodological, theoretical, and personal.
The result is a truly original book, one that displays a particular way of practicing the human sciences and thus a particular - and particularly efficacious - view of what these sciences are, have been, and should become.
Includes bibliographical references and index.
Keywords: Geertz, Clifford; Anthropologists -- United States -- Biography; Anthropologists -- Asia -- Biography; Philosophical anthropology; Asia -- Social conditions; Africa -- Social conditions